Home is the new gym: exergame as a potential tool to maintain adequate fitness levels also during quarantine - Cortis, C.; Giancotti, G. F.; Rodio, A.; Bianco, A.; Fusco, A. (Human Movement, 2020)
Purpose: With the coronavirus outbreak, the preventive measures include staying at home and isolation, increasing sedentary behaviours and risk for worsening of chronic diseases. To explore alternative forms of home-based physical activity, the study aim was to evaluate physiological (heart rate [HR], respiratory exchange ratio [RER], oxygen consumption [VO2], Energy expenditure [EE], metabolic equivalent task [MET]) and psychological (session rating of perceived exertion [sRPE], enjoyment) parameters of real (Zumba® class [ZC]) and exergame (Zumba® Fitness Rush [ZFR]) activities in relation to sex.